Valuation of marine ecosystems and Sustainable Development Goals - Koundouri, Phoebe; Halkos, George; Landis, Conrad; Dellis, Konstantinos; Stratopoulou, Artemis; Plataniotis, Angelos; Chioatto, Elisa (Frontiers in Environmental Economics, 2023)
This paper refers to the valuation of European, Marine and Fresh Water Ecosystem Services. Using a meta-regression approach, we estimate the Annual Willingness to Pay (WTP) for several classifications of the ecosystem services and various biogeographical and marine regions across all 27 EU markets. Moreover, we explore the correlation between WTP and the national level of achievement of the 17 SDGs, with particular focus on SDG 14—Life Below Water. Results indicate that regulating services of marine and freshwater ecosystems are ranked high and that in almost 63% of the European countries, the WTP for the improvement of the marine and freshwater ecosystem is high and exceeds estimates for terrestrial ecosystems. Valuing ecosystem services and link them to the Sustainable Development Goals, we find that marine ecosystems are mainly positively correlated to SDGs 2, 12, 13, 14, and 17, while a high MWTP value is assigned to specific SDG14 individual indicators like fish caught from overexploited or collapsed stocks and fish caught that are then discarded. Overall, results indicate that societies attributing greater value to ecosystem services mark greater progress toward the implementation of SDGs and SDG 14 in particular.